Reform, financing, and business model of artisanal public transport in West Africa: A comparative analysis of minibus networks in Dakar, Bamako, and Conakry - Diaou, Elhadji Ibrahima; Naringué, François Teadoum; Vimenyo, Messan; Diene, Mbaye (Edelweiss Applied Science and Technology, 2026)
The main objective of this study is to analyze the extent to which reform based on minibus renewal improves operators' operating methods, profitability, and access to formal financing. It is based on a comparative analysis between old minibus networks (OMN), such as the “cars rapides/ndiaga ndiaye” in the Senegalese capital, the “sotramas” in Bamako, and the “magbanas” in Conakry, and a new minibus network (NMN), namely the Urban Transport Funding Association (AFTU), created as part of the minibus fleet renewal program in Dakar. The methodology adopted combines statistical analysis of data from field surveys of minibus operators and semi-directive interviews with key stakeholders in the sector. The results reveal improved structuring of reformed minibuses, which has promoted the social inclusion of actors in the AFTU network, the transformation of their business model, and the bancarization of vehicle owners, who are now able to access formal financing enabling them to invest in reliable and high-capacity rolling stock. This study highlights the decisive role that reforming paratransit financing can play in modernizing the operational practices of artisanal networks. It is a strategic lever for promoting the gradual formalization of actors into professional transport companies, in line with the objectives of sustainable urban mobility.